Developing an Ear Health Intervention for Rural Community Pharmacy: Application of the PRECEDE-PROCEED Model - Taylor, Selina (Int J Environ Res Public Health, 2021)
Unaddressed hearing loss affects an estimated 466 million people worldwide, costing over $750 billion globally, with rural communities being particularly disadvantaged, due to the greater inequity in access to healthcare services. This mixed-methods study aimed to use the PRECEDE-PROCEED model to develop and pilot a rural community pharmacy-based ear health service, LISTEN UP (Locally Integrated Screening and Testing Ear aNd aUral Program). The PRECEDE process involved an assessment of the predisposing, reinforcing and enabling constructs to support practice change through a scoping review, stakeholder surveys and interviews and consultation with governing bodies and regulatory authorities. The PROCEED segment structured the evaluation of the service pilot and informed planned implementation, process, impact and outcome evaluation. The pilot study conducted in February 2021 included 20 participants, with the most common ear complaints presented being pain, pressure or blockage. All these participants reported high levels of satisfaction with the service, would recommend the service to others and would attend the pharmacy first before seeing a GP for future ear complaints. The PRECEDE-PROCEED model provides a comprehensive model to guide the design of the LISTEN UP program, an innovative model, expanding services offered by rural community pharmacies, with preliminary results demonstrating high consumer satisfaction.